2016
DOI: 10.18632/oncotarget.10583
|View full text |Cite|
|
Sign up to set email alerts
|

Prorenin receptor acts as a potential molecular target for pancreatic ductal adenocarcinoma diagnosis

Abstract: Recent studies have implicated the prorenin receptor (PRR) is associated with pancreatic tumorigenesis. We therefore investigated the role of PRR in pancreatic tumorigenesis and assessed whether PRR can serve as a target for imaging diagnosis at early stages of PDAC. Here we show that aberrant expression of PRR in premalignant PanIN lesions, and human PDAC samples, and PDAC cell lines, particularly in Panc-1 cells. Interestingly, PRR expression was positively associated with PDAC progression. Moreover, overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Additionally, (P) RR induces reactive oxygen species (ROS) formation, which is independent of Ang II, thus further contributing to MAPK/ERK and PI3K/ AKT/mTOR signal transduction [31]. Consistent with these observations, Arundhathi et al [32] investigated the function of (P) RR in the biological activities of the human pancreatic cancer cell lines Panc-1 and ASPC and found that (P) RR exerts a cancer-promoting effect by enhancing activity in the MAPK/ERK and PI3K/AKT/mTOR signaling pathways. In particular, the data from this group showed that (P) RR overexpression increased the phosphorylation of AKT, ERK1/2, and mammalian target of rapamycin (mTOR) and elevated the level of NF-κB; however, (P) RR silencing downregulated the expression of ERK1/2, AKT and NF-κB [32] in pancreatic cancer cells.…”
Section: The Mapk/erk and Pi3k/akt/mtor Pathwaysmentioning
confidence: 69%
See 3 more Smart Citations
“…Additionally, (P) RR induces reactive oxygen species (ROS) formation, which is independent of Ang II, thus further contributing to MAPK/ERK and PI3K/ AKT/mTOR signal transduction [31]. Consistent with these observations, Arundhathi et al [32] investigated the function of (P) RR in the biological activities of the human pancreatic cancer cell lines Panc-1 and ASPC and found that (P) RR exerts a cancer-promoting effect by enhancing activity in the MAPK/ERK and PI3K/AKT/mTOR signaling pathways. In particular, the data from this group showed that (P) RR overexpression increased the phosphorylation of AKT, ERK1/2, and mammalian target of rapamycin (mTOR) and elevated the level of NF-κB; however, (P) RR silencing downregulated the expression of ERK1/2, AKT and NF-κB [32] in pancreatic cancer cells.…”
Section: The Mapk/erk and Pi3k/akt/mtor Pathwaysmentioning
confidence: 69%
“…Consistent with these observations, Arundhathi et al [32] investigated the function of (P) RR in the biological activities of the human pancreatic cancer cell lines Panc-1 and ASPC and found that (P) RR exerts a cancer-promoting effect by enhancing activity in the MAPK/ERK and PI3K/AKT/mTOR signaling pathways. In particular, the data from this group showed that (P) RR overexpression increased the phosphorylation of AKT, ERK1/2, and mammalian target of rapamycin (mTOR) and elevated the level of NF-κB; however, (P) RR silencing downregulated the expression of ERK1/2, AKT and NF-κB [32] in pancreatic cancer cells. Taken together, these findings indicate that (P) RR may contribute to cancer development through the MAPK/ERK and PI3K/AKT/mTOR pathways (Fig.…”
Section: The Mapk/erk and Pi3k/akt/mtor Pathwaysmentioning
confidence: 74%
See 2 more Smart Citations
“…Renin and its precursor pro-renin bind to pro-renin receptor (PRR) to activate the MAPK signaling cascades. PRR is associated with increased cell proliferation, decreased apoptosis and highly expressed in pancreatic ductal adenocarcinoma [25] . CSC subpopulations in GB [26] and OCSCC of different subsites [27][28][29] express components of RAS.…”
Section: Introductionmentioning
confidence: 99%